Absorptive Capacities and Innovation in Graduated Companies from a Business Incubator in the North of Mexico - León Ramírez, Valeria Carolina; Velarde Flores, Cecilia Lorena; Rodríguez Borbón, Marisol; Valdez del Río, Sacnicté; Nuñez Ramírez, Marco Alberto (International Journal of Advanced Corporate Learning (iJAC), 2018)
The aim of this research is to identify the relationship between absorptive capacities and the generation of innovation, as well as their level of influence in companies graduated from an incubator in the north of Mexico. Through a quantitative research, correlational with a non-experimental design, a sample of 100 companies was obtained. The hypotheses of the study were partially approved, finding that the entrepreneurs were able to acquire, assimilate and transform the process of absorptive capacity, generating incremental innovation which is an intangible asset with high value for organizations.